Seismic Response Reduction of Structures Equipped with a Voided Biaxial Slab-Based Tuned Rolling Mass Damper. (14th June 2015) - Li, Shujin; Fu, Liming; Kong, Fan
Abstract : This paper proposes a novel tuned mass damper (TMD) embedded in hollow slabs of civil structures. The hollow slabs in this context, also referred to as "voided biaxial reinforced concrete slabs, " feature a large interior space of prefabricated voided modules that are necessary in the construction of this special structural system. In this regard, a tuned rolling mass damper system ("TRoMaDaS") is newly proposed, in combination with hollow slabs, to act as an ensemble passive damping device mitigating structural responses. The main advantage of this TMD configuration lies in its capacity to maintain architectural integrity. To further investigate the potential application of the proposed TRoMaDaS in seismic response mitigation, theoretical and numerical studies, including deterministic and stochastic analyses, were performed. They were achieved by deterministic dynamic modeling using Lagrange's equation and the statistical linearization method. Finally, the promising control efficacy obtained from the deterministic/stochastic analysis confirmed the potential application of this newly proposed control device.